Adolescents and Sexual Violations Online. (28th September 2020) - Sivan Holst, Nicolaj; Adolphsen, Caroline
Abstract: The article describes and discusses sexual violations online using the recent Danish case law and legislation as an example and drawing upon the United Nation Convention on the Rights of the Child. It is argued that the legislation does not provide a sufficient solution to the problems connected to digital violations of the physical integrity of the victim.